Analysis of the Business Environment in Formulating Marketing Strategy and The Impact on Sales and Financial Performance in the Post COVID 19 Pandemic - Syaifuddin , Syaifuddin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The current environmental changes as a result of the COVID-19 pandemic and entering the